Corrections to "pairwise s-normal spaces" rev. colombiana mat. 26 (1992), 25-38 (1993)
The following corrections are necessary in the paper:1. Example 2.1.1. is not pairwise normal since {0} is T1-closed and N is T2-closed and a T2-open subset containing {0} intersects with any T1-open set containing N.